2021
DOI: 10.1029/2021jb022080
|View full text |Cite
|
Sign up to set email alerts
|

Elastic Geobarometry for Anisotropic Inclusions in Anisotropic Host Minerals: Quartz‐in‐Zircon

Abstract: Solid mineral inclusions entrapped within a host mineral can retain physical and chemical information from the pressure (P)-temperature (T) conditions of entrapment and evolution during subsequent metamorphism. In addition to conventional thermobarometric methods (i.e., exchange thermobarometry, equilibrium assemblage modeling, etc.), application of elastic models to determine the metamorphic conditions of inclusion entrapment have become commonly used petrologic methods (e.g.,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Therefore, cooling cannot be responsible for the birefringent haloes seen in diamonds when observed at room temperature. This was confirmed by the analysis (Goodier, 1933) of the stress developed in and around inclusions when the host is subject to an external stress, which include changes in external hydrostatic pressure and the effective stress generated as the result of cooling. Goodier (1933) showed that, starting from a system in uniform stress and strain, the final stress state is determined solely by the elastic properties of the system and the volume strain imposed on the host.…”
Section: A Brief Historymentioning
confidence: 64%
“…Therefore, cooling cannot be responsible for the birefringent haloes seen in diamonds when observed at room temperature. This was confirmed by the analysis (Goodier, 1933) of the stress developed in and around inclusions when the host is subject to an external stress, which include changes in external hydrostatic pressure and the effective stress generated as the result of cooling. Goodier (1933) showed that, starting from a system in uniform stress and strain, the final stress state is determined solely by the elastic properties of the system and the volume strain imposed on the host.…”
Section: A Brief Historymentioning
confidence: 64%
“…The field of elastic geothermobarometry is continuing to develop rapidly, and a recently introduced model for anisotropic mineral inclusions in anisotropic host minerals by Gonzalez et al (2021) gives cause for optimism to cope complex systems in future. However, the subject of coesite-in-garnet has not been touched so far.…”
Section: Elastic Geothermobarometrymentioning
confidence: 99%